Improving the Quality and Shelf Life of Tauco at CV Tauco Cap "Meong" Cianjur Through Thermal Treatment and Formulation Enhancement - Parlan; Bambang Nurhadi; Nandi Sukri; Rudy Adi Saputra (International Journal of Business, Economics, and Social Development, 2025)
Traditional fermented foods like tauco play a significant role in Indonesian culinary heritage. However, many micro and small enterprises (MSEs) face challenges related to inconsistent product quality and short shelf life. Tauco Cap “Meong,” a local producer in Cianjur, West Java, experiences similar limitations due to spontaneous fermentation, high water activity (Aw), and inadequate thermal treatment. These issues lead to microbial instability and sensory degradation during storage. This community engagement project aimed to optimize tauco production by improving formulation, introducing food-grade preservatives (BTP), and applying controlled thermal processing. The interventions included pH adjustment using 0.75% food acid, Aw reduction through thermal treatment, and the addition of stabilizers such as 0.1% CMC and xanthan gum, followed by hot filling and sealed packaging. Results showed that pH adjustment successfully lowered the pH from 4.6 to 4.3–4.4, shifting the product into a lower-risk microbial category while maintaining favorable color, aroma, and viscosity. Aw was reduced from 0.89 to 0.87 and 0.79 with 15 and 23 minutes of heating, respectively, although over-thickening and darker color were observed in the latter. After 75 days of storage, treated samples showed no phase separation or spoilage, with final Aw at 0.806 and total plate counts (TPC) of 1.5 × 10⁴ CFU/g, significantly lower than untreated controls. Sensory quality, particularly homogeneity and aroma, remained acceptable throughout storage. These improvements demonstrate the feasibility of simple, low-cost technological interventions to extend shelf life and enhance product stability in small-scale fermented food production.